2015
DOI: 10.1093/infdis/jiv066
|View full text |Cite
|
Sign up to set email alerts
|

Limited Efficacy of Antibacterial Vaccination Against Secondary Serotype 3 Pneumococcal Pneumonia Following Influenza Infection

Abstract: The results show that induction of antibacterial humoral immunity is only partially effective in protection against secondary bacterial infections that occur following influenza, and suggest that additional therapeutic strategies to overcome defective antibacterial immunity should be explored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 28 publications
1
37
0
Order By: Relevance
“…Although influenza virus and pneumococcus coinfection is responsible for higher mortality and morbidity, the current pneumococcal conjugate vaccine does not provide sufficient protection in the serial coinfection model (Metzger et al 2015). Therefore, the development of a new type of vaccine, which can protect against influenza virus and pneumococcus coinfection, is required.…”
Section: Factors Increasing Pneumonia Risk In Pneumococcal Infectionsmentioning
confidence: 99%
“…Although influenza virus and pneumococcus coinfection is responsible for higher mortality and morbidity, the current pneumococcal conjugate vaccine does not provide sufficient protection in the serial coinfection model (Metzger et al 2015). Therefore, the development of a new type of vaccine, which can protect against influenza virus and pneumococcus coinfection, is required.…”
Section: Factors Increasing Pneumonia Risk In Pneumococcal Infectionsmentioning
confidence: 99%
“…In contrast, following vaccination against IAV viral exposure may still impair host defenses sufficiently to promote bacterial superinfection, even in the absence of a clinically apparent viral infection. Interestingly, a recent report using a conjugate vaccine against S. pneumoniae showed that this vaccine did not result in 100% protection as obtained with the anti-M protein vaccine (Metzger et al, 2015 ). This indicates that there is still much to learn regarding the differences in the pathogenesis of IAV-bacterial superinfections and the contributions of vaccine-induced immunity in the context of polymicrobial infections.…”
Section: Mechanisms Of Iav-gas Superinfectionmentioning
confidence: 99%
“…SBIs, in particular, have accounted for 40–95 % of influenza-related mortality in past pandemics [4, 17, 29, 48]. Vaccines against bacterial pathogens can reduce the coinfection component [15, 25, 27], but their efficacy is limited to the vaccine strains and some bacterial vaccines have reduced effectiveness in influenza virus-infected hosts [25, 27]. Treatment with antimicrobial agents may also improve disease outcome and reduce SBI incidence [7, 8, 12, 13, 18, 21, 26], but many provide only partial protection, have time dependent efficacy, and/or cause adverse effects.…”
Section: Introductionmentioning
confidence: 99%